DEVELOPMENT OF MILK PRODUCTION INFORMATION SYSTEM FOR DAIRY COWS IN BALAI BESAR PELATIHAN PETERNAKAN (BBPP) BATU - , RACHMASARI CAHYANINGDYAH, Mardhani Riasetiawan, SE Ak MT ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Balai Besar Pelatihan Peternakan (BBPP) Batu is a training institution for farmers which have a cattle breeding as training facilities. The training includes recording training in order to make the better decision in the next step of animal husbandry. Recording of milk production is an important recording beside animal healthâs recording, because it used to know total milk production and its distribution in some report. Recording of milk production system that used in Kesehatan Hewan dan Reproduksi of Balai Besar Pelatihan Peternakan (BBPP) is still minimal, which use paper to save the record. Its similar with recording of milk distribution. After that, it used to make report based on the squeezing month and count the total of milk distribution to get milk distribution report. Based on the problem above, information system is needed to solve the recording process until make the report. This information system is built using codeigniter framework, MySQL database and framework jQuery for javascript. Beside that, this system also shown the report of recording in the form of graphs. Milk production information system for dairy cows in Balai Besar Pelatihan Peternakan (BBPP) Batu can used to control milk recording and its reports, quality of milk production report and milk distribution report.